2014
DOI: 10.1016/j.jelechem.2014.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetry at porous electrodes: A theoretical study

Abstract: Theory is presented to simulate both chronoamperometry and cyclic voltammetry at porous electrodes fabricated by means of electro-deposition around spherical templates. A theoretical method to extract heterogeneous rate constants for quasireversible and irreversible systems is proposed by the approximation of decoupling of the diffusion within the porous electrode and of bulk diffusion to the electrode surface.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 36 publications
4
43
0
Order By: Relevance
“…more in proximity of the solution bulk). This effect was previously observed by us [10] and simulated by Barnes et al [15], the latter having modelled the chronoamperometric behaviour of a porous electrode on which a mass transport control reaction occurs. In this work, the authors observe an initial period in which thin layer diffusion within the layer sums to planar/semi-infinite one.…”
Section: Insert Figure 2 Heresupporting
confidence: 72%
“…more in proximity of the solution bulk). This effect was previously observed by us [10] and simulated by Barnes et al [15], the latter having modelled the chronoamperometric behaviour of a porous electrode on which a mass transport control reaction occurs. In this work, the authors observe an initial period in which thin layer diffusion within the layer sums to planar/semi-infinite one.…”
Section: Insert Figure 2 Heresupporting
confidence: 72%
“…FC has a straightforward redox behavior with a fast HET that is known to be sensitive to electrode surface conditions [21,23]. CVs of FC using SPCE (SPCE-CNT prist or SPCE-CNT ox,8 h ) are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MM3 explicitly accounts for hydrogen bond interactions and is one of the most accurate force fields for graphitic materials [29]. 1 This equation validity is limited by thin-layer effects associated to the porosity of the CNT layer [20,21]. Three different molecules in oxidized and reduced forms were studied: p-Q, o-quinone (o-Q) and DA.…”
Section: Resultsmentioning
confidence: 99%
“…However, it was seen that the charge storage capacity was diminished at high discharge rates. Computational modeling of Faradaic process in porous electrodes has found that reduced capacity may be due to planar diffusion to the exterior surface [312] and not within the pores of the electrode itself.…”
Section: Faradaic Energy Storage In Nanoscale Confined Electrolytesmentioning
confidence: 99%